Extraction of total polyphenols from hibiscus (Hibiscus sabdariffa L.) and waxweed / `sete-sangrias´ (Cuphea carthagenensis) and evaluation of their antioxidant potential - Begmeier, Daniele; Berres, Pedro Henrique Dalberto; Filippi, Débora; Bilibio, Denise; Bettiol, Vanderlei Rodrigo; Priamo, Wagner Luiz (Acta Scientiarum. Technology, 2014)
Current research investigates the extraction process of total polyphenols from hibiscus (Hibiscus sabdariffa L.) and waxweed (Brazilian name: `sete-sangrias´) (Cuphea carthagenensis) and evaluates the antioxidant potential of their extracts. The extraction stage comprised investigation on the following parameters: i) solvents (acetone and ethanol) pure and fractioned with water; ii) variables (temperature, stirring, solvent ratio, time and pH). Total polyphenols were quantified by Folin-Ciocalteau reagent and antioxidant activity was determined by ABTSâ€¢+ (2,2â€²-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) and DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging assay. Results showed that, depending on experimental conditions, total phenolic contents for hibiscus and waxweed ranged between 460.86 mg GAE 100 g-1 and 5012.54 mg GAE 100 g-1 and between 462.86 mg GAE 100 g-1 and 4215.99 mg GAE 100 g-1, respectively. Waxweed had a higher antioxidant activity when compared to that of hibiscus by both ABTSâ€¢+ and DPPH. Data showed that hibiscus and waxweed have a significant amount of polyphenols which may be extracted in mild processing conditions and then employed as natural antioxidant sources in industrial processes.